Design of a low speed vaneaxial fan - Andreadis, Eleftherios (Cranfield University, 2011)
The ventilation of industrial areas and tunnels is a safety requirement and characterizes the quality of a working environment. Low speed fans are used to achieve the required ventilation level. An attempt to design a low speed vaneaxial fan, meeting the specifications of a given fan that is already in the market takes place in this Thesis. The project was conducted with the support of the Fläkt-Woods Company and the main target is to design a ventilation fan, meeting the requirements for pressure rise, volume flow and size, of an existing model. The efficiency improvement is driven in part by the new national and international legislation concerning the operation of electrical equipment. Companies require higher efficiencies without compromising safety features of the fan and the fan capability to operate at high temperatures. A low speed fan design procedure is established based on the available literature and design tools. The free vortex approach is employed, which provides acceptable efficiency and relatively simpler design. The design procedure can be used to design a fan given a set of customer requirements. Many software tools are used to design the fan. A Matlab code for the blade design is developed and other codes are used to establish the final fan design. The effectiveness of the design procedure is verified with CFD simulations carried out as part of this project. Three new designs that are developed with the established design procedure are presented in this Thesis. The new designs differ in the hub to tip ratio, the rotational speed and the number of the blades and the vanes. The experience acquired from the analysis of the performance of the first new design is used to improve the performance of the following designs in order to achieve the best efficiency possible. The effect of tip clearance is investigated thoroughly in the new designs because the tip clearance has a major impact on the fan performance and safe operation of the fan at high temperatures. The mechanical integrity of the fan is examined last to verify that the fan can operate in high temperature. The target of improved efficiency (higher than 79%) is achieved in one of the fan designs attempted and it was calculated 82%. The off design performance of the new fan is satisfactory as well. This new design can be further optimized, since the modification of minor design features is in itself a methodology that can incrementally improve the efficiency of a low speed fan. The new fan can operate at high temperatures (400°C), however the safety factor at this temperature is 1.25 for combined steady mechanical and thermal loading and it can be further improved either through the use of materials with better resistance in thermal loading or with an increased tip clearance.